Temporal evolution in synthetic handwriting. (August 2017) - Carmona-Duarte, Cristina; Ferrer, Miguel A.; Parziale, Antonio; Marcelli, Angelo
Highlights: Method of synthesizing the temporal evolution of handwriting from childhood to adulthood. Synthesis of both online and offline handwriting. Parameters (E, ɛ D, ɛ t, Kσ ) for dealing with synthesized handwriting evolution. Method for comparing temporal evolution of real and synthetic handwriting. Abstract: New methods for generating synthetic handwriting images for biometric applications have recently been developed. The temporal evolution of handwriting from childhood to adulthood is usually left unexplored in these works. This paper proposes a novel methodology for including temporal evolution in a handwriting synthesizer by means of simplifying the text trajectory plan and handwriting dynamics. This is achieved through a tailored version of the kinematic theory of rapid human movements and the neuromotor inspired handwriting synthesizer. The realism of the proposed method has been evaluated by comparing the temporal evolution of real and synthetic samples both quantitatively and subjectively. The quantitative test is based on a visual perception algorithm that compares the letter variability and the number of strokes in the real and synthetic handwriting produced at different ages. In the subjective test, 30 people are asked to evaluate the perceived realism of the evolution of the synthetic handwriting.